Feeding in extinct jawless heterostracan fishes and testing scenarios of early vertebrate evolution - Purnell, Mark A. (Proceedings of the Royal Society. B, Biological sciences, 2002)
How long-extinct jawless fishes fed is poorly understood, yet interpretations of feeding are an important component of many hypotheses concerning the origin and early evolution of vertebrates. Heterostracans were the most diverse clade of armoured jawless vertebrates (stem gnathostomes), and the structure of the mouth and its use in feeding are the subjects of long-standing and heated controversy. I present here evidence that heterostracan feeding structures exhibit recurrent patterns of in vivo wear, are covered internally by microscopic oral denticles, and that the mouth may have been less flexible than has been thought. These data, particularly the absence of wear at the tips of oral plates, and the evidence that the mouth was lined with delicate outwardly directed denticles, effectively falsify all but one hypothesis of feeding in heterostracans: heterostracans were microphagous suspension feeders. This has a direct bearing on hypotheses that address ecological aspects of early vertebrate diversity and evolution, contradicting the widespread view that the pattern of early vertebrate evolution reflects a long-term trend towards increasingly active and predatory habits.